Frontiers in Toxicity and Functionalization of Nanomaterials - Dong-Wook Han (Ed.); Wojciech Chrzanowski (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Over the last decade, various nanomaterials (NMs) have attracted tremendous attention with the incredible development in nanoscience and nanotechnology. Some NMs are explored increasingly for biomedical applications, including drug delivery carriers, imaging probes, antimicrobial agents, biosensors, and tissue engineering scaffolds. However, the in vitro and in vivo toxicities of NMs related to oxidative stress are the main obstacles to use them in biomedical fields. One of the most promising strategies to address these obstacles is functionalizing NMs with biocompatible molecules or materials. In this Special Issue, we are especially interested in manuscripts that advance the understanding of the interaction of NMs with cells, such as cellular responses to NMs, intracellular behaviors of NMs, therapeutic and imaging potentials of NMs, as well as the functionalization of NMs through coating, patterning and hybridization with other biomolecules for multifaceted biomedical applications.
English
Keywords: Nanotoxicity; Nanomaterial functionalization; Biomedical applications; Cell-nanomaterial interactions; Biocompatibility